The Kromdraai early hominin-bearing site. A review of recent findings - (:unkn) unknown (My University, 2022)
The Kromdraai archaeological site is located in a fossiliferous paleokarst situated in the UNESCO World Heritage Site referred to as the “Cradle of Humankind” in the Gauteng Province of South Africa. Kromdraai is noteworthy because it features among the three southern African early hominin-bearing sites considered to represent distinct temporal periods within the same stratigraphic succession. Kromdraai also yielded a partial skull and dentition (TM 1517) in 1938 that was designated as the holotype of a new genus and species, Paranthropus robustus. Although the hominin fossil assemblage collected from Kromdraai between 1938 and 2014 is rather paltry, morphometric and cladistic analyses of this material suggested that it represented a somewhat less-derived form of P. robustus than the considerably larger assemblage from the nearby site of Swartkrans. However, the geochronological and biotic relationships among the P. robustus-bearing sites in South Africa are not resolved. Since 2014, the previously unknown, albeit densely fossiliferous Unit P produced 51 individually catalogued hominin fossils (36 craniodental and 15 postcranial) that currently represent 13% of the faunal assemblage from this unit with a minimum number of 10 juvenile and 9 adult individuals. P. robustus and early Homo coexisted at the time of the accumulation of Unit P at Kromdraai, with a relative abundance of 89% and 11%, respectively. P. robustus and early Homo are associated with a highly diverse fauna that includes several water-dependent species, and a large variety of bovid and carnivore taxa. Biochronological data from Unit P and an interval of reversed polarity measured in younger deposits above it are interpreted in the context of the regional chronological framework to infer that it represents a deposit that was likely accumulated prior to 2 Ma.
Keywords: African Research